Do the Islamic banks play a role in the monetary policy transmission in Pakistan? A comparative analysis with conventional banks using panel data analysis - Farhad Ahmed Bhatti; Salina Kassim; Razali Haron (USIM Press, 2024)
Vol. 19, No. 2 Page (13-27)